Trend and Pattern of Cereal Crops: Production, Productivity and Area Coverage in Nepal (Patan Pragya, 2019)
This study conducted to examine growth trends and pattern in area, production and productivity of major cereal crops over the six fiscal years. Time series data of cereal crops coverage of annual yield were used for the study. This study was based on descriptive nature and used secondary sources of information on production, productivity and area coverage of major cereals (Paddy, Maize, Wheat, Millet, Buckwheat and Barley) covering the six fiscal years (2011/12-20116/17) data. Trends of crop's productivity were analyzed using graphical methods. Ratio and percentage were used to measure productivity (yield) growth rate of the selected crops of study. The yielding trend of cereal production is not satisfactory in Nepalese economy. Pattern of agricultural production in Nepal is affected by multiple factors including rugged topography, monsoon, insignificant investment in infrastructure, and research and development. Production and productivity would be helpful to develop the future plans and take the appropriate decisions to uphold the situation for the sustainability in food production.